Nature and origin of sapropels in the Quarternary sediments of the Cilician Basin, NE. Mediterranean - Ali , Zulfiqar; Haneef, Mohammad (Journal of Himalayan Earth Sciences, 1993)
Dark, finely laminated, organic-rich sapropelic horizons are the most striking features of the Cilician Basin sediments as revealed by the radiographic and geochemical investigations. TOC of these horizons occur in the range of 0.8-1.52%, is lower than the previously reported values of TOC from the S1 sapropels in the Meditaranean Basin. AOM are intensely degraded except in one core, where partially Preserved AOM are observed. Teresterial OM are comparatively Preserved. The degraded nature of OM suggests that the condition for OM preservation is not favorable. However, the fine lamination and absence of benthic organisms are the evidence in favour of anoxic conditions leading to the formation of sapropelic horizons. The idea that anoxia favouring the 0M preservation is the cause of sapropelic formation is not supported in Present work. These layers are Presumed to have been formed during Post-Glacial climatic warming as a result of high input of terresterial OM and increased bilogical productivity. Abbreviations: Organic matter (OM), Amorphous organic matter (AOM), Terresterial organic matter (TOM), Total organic carbon (TOC), Pleistocene-Holocene Sapropels of the Mediterranean (Y).